Examination and analysis of researcher-participant power dynamics in focus group discussions - Nduna, Mzikazi (PINS-Psychology in Society, 2022)
Focus group discussions (FGDs) are a popular method of collecting data for various qualitative research study designs. The value of focus group discussions (FGDs) in community-based studies is enhanced with rigorous application of the research method. Its flexibility enhances its usefulness in varied contexts, research questions and disciplines. However, power dynamics could affect optimum use of the method, the kind and amount of data collected. Based on research experience mainly in South African communities; villages and townships, this paper explores the performance of power in FGDs. This paper discusses researcher-participant power dynamics in community engagement, participant recruitment, organisation and facilitation of FGDs. The experiences discussed here are applicable in a variety of research topics, and beyond the South African context.